1998
DOI: 10.3181/00379727-219-44327
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity of Murine Retrovirus Infected C57BL/6 Mice is Prevented by Melatonin and Dehydroepiandrosterone

Abstract: LP-BM5 retrovirus infection and hormone synthesis modulate many physiological systems that could affect physical activity. Infection induced oxidative damage and immunodeficiency of female mice which hormone supplement prevented. Therefore, the effects of retrovirus infection and hormone supplementation were assessed on physical activity using a computerized video system. Retroviral infection increased activity when stationary while lowering average speed and resting time. Hormone supplementation partially mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In a follow-up study (to be reported elsewhere) we recently determined that similar melatonin treatment again increased (P Ͻ 0.05) spontaneous locomotor activity in middle-aged male rats by 18%. Although a specific mechanism for this effect of melatonin is not clear, melatonin treatment has been found to reverse the decreased physical activity of old mice (24), of rats with suppressed endogenous melatonin secretion due to continuous light exposure (25), and of mice infected with murine retrovirus (26). Recent work (20) has shown that small changes in physical activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study (to be reported elsewhere) we recently determined that similar melatonin treatment again increased (P Ͻ 0.05) spontaneous locomotor activity in middle-aged male rats by 18%. Although a specific mechanism for this effect of melatonin is not clear, melatonin treatment has been found to reverse the decreased physical activity of old mice (24), of rats with suppressed endogenous melatonin secretion due to continuous light exposure (25), and of mice infected with murine retrovirus (26). Recent work (20) has shown that small changes in physical activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study (to be reported elsewhere) we recently determined that similar melatonin treatment again increased (P Ͻ 0.05) spontaneous locomotor activity in middle-aged male rats by 18%. Although a specific mechanism for this effect of melatonin is not clear, melatonin treatment has been found to reverse the decreased physical activity of old mice (24), of rats with suppressed endogenous melatonin secretion due to continuous light exposure (25), and of mice infected with murine retrovirus (26). Recent work (20) has shown that small changes in physical activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin administration not only reduced the mortality rate from these viruses, but also significantly postponed onset of disease ( 10 ), providing further evidence of melatonin use as treatment in a number of viral diseases. There is some research concerning the effects of melatonin on retroviruses such as HIV and murine model retroviruses such as LP-BM5 and Ts1, though these do not seem to have many pertinent similarities to COVID-19 ( 32 , 33 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%